The effect of retinopathy of prematurity on visual acuity, refraction, biometric values, retinal and choroidal thickness in school-aged children - Kılınç, Ali Kutay; Ozdemir, O.; Acar, D. E.; Işık, M. U. (Springer Science and Business Media LLC, 2025)
This study aimed to investigate the long-term effects of retinopathy of prematurity (ROP) on visual function and ocular anatomy. We compared biometric values, foveal thickness, and choroidal thickness among children with a history of ROP (stratified by treatment status), premature infants without ROP, and term-born children.This cross-sectional study was conducted between september 2021 and february 2022 at the Ophthalmology Department of Ankara Bilkent City Hospital. The study included 54 eyes from 29 children who received laser photocoagulation treatment for ROP (ROP-Tx Group), 52 eyes from 26 children who developed ROP but did not require treatment (ROP-nonTx Group), 51 eyes from 25 children born prematurely without ROP (Premature Group), and 54 eyes from 27 healthy term children of the same age group (Control Group). One eye of a single premature infant was included in the ROP-nonTx group, while the other eye was included in the Premature group. The first three groups included patients who were followed up under the Retinopathy of Prematurity protocol at Zekai Tahir Burak Hospital between 2008 and 2016, while the control group consisted of 5-12 years old who presented for a routine eye examination without any ocular complaints or history of prematurity. Non-cycloplegic and cycloplegic refractive errors, best corrected visual acuity (BCVA), keratometry, axial length (AL) and anterior chamber depth (ACD), optical coherence tomography (OCT) central macula and choroid thickness measurements were performed in all cases.Premature infants treated with laser photocoagulation for retinopathy of prematurity exhibited significant differences in all measured ocular parameters compared to the term-born control group (p < 0.05). These parameters included reduced best corrected visual acuity (0.1 logMar), steeper keratometry values (K2: 47.95 Dioptre, K1: 45.83 Dioptre), more myopic spherical equivalent (-0.87 Dioptre), shorter axial length (21.67 mm), decreased anterior chamber depth (3.04 mm), as well as increased central macular thickness (300.50 μm) and decreased central choroidal thickness (268.27 μm). Infants who developed ROP but did not require laser treatment also exhibited significant differences compared to the control group, including steeper keratometry values (K2: 46.62 Dioptre, K1: 45.24 Dioptre) shorter axial length (22.01 mm), and increased central macular thickness (250.05 μm). Interestingly, anterior chamber depth was significantly unexpected way different (3.47 mm) only in the premature group without ROP compared to the term-born controls (p < 0.05).The study found that prematurity, ROP, and eye development are closely connected. Premature infants who treated with laser photocoagulation for ROP had the most significant differences in eye structure and vision compared to full-term infants. Even premature infants who showed spontaneous regression of ROP still demonstrated differences in ocular anatomy. These results emphasize the importance of closely monitoring premature infants, especially those treated for ROP, to ensure their vision develops properly.
Keywords: Male; Biometry; Visual Acuity; Gestational Age; Refraction, Ocular; Retina; Foveal thickness; Humans; Retinopathy of Prematurity; Laser photocoagulation; Child; Laser Coagulation; Choroid; Research; Infant, Newborn; RE1-994; Ophthalmology; Cross-Sectional Studies; Choroidal thickness; OCT; Child, Preschool; Female; Prematurity; Tomography, Optical Coherence; Infant, Premature; Follow-Up Studies